Faʿāliyyatu Wasīlati Spinning Wheel fī Taḥsīni Natāʾiji Taʿlīmi al-Naḥwi fī al-Madrasah al-Mutawassiṭah al-Islāmiyyah Bustān al-ʿUlūm al-Surūr Sumber Jambe li al-Sanah al-Dirāsiyyah 2022/2023 M: The Effectiveness of the Spinning Wheel Medium in Improving Grammar Learning Outcomes at Bustanul Ulum As-Surur Islamic Junior High School, Sumber Jambe, for the 2022/2023 Academic Year - Muqit, Abdul; Ruswatie, Ade (Critical Review of English-Arabic World Journal, 2023)
Spinning wheel learning media is a learning media in the form of a spinning wheel containing questions that combines the ability to answer questions with the insights that students already have. As a result of personal interviews with Arabic teachers, researchers obtained academic information that there are still many students who have difficulty learning Arabic, especially in qawaid nahwu. The researcher took the title of this study because of the problems that occur among students who lack enthusiasm in learning nahwu so that learning outcomes are not optimal. Therefore, researchers consider that spinning wheel learning media is very suitable for this problem. The purpose of this study are: To determine the effectiveness of Spinning Wheel learning media in improving nahwu learning outcomes. Researchers use quantitative research approaches and types of experimental research, as well as data collection methods through observation, tests, and documentation. Data analysis method using t-test code. The results of this research mean the application of spinning wheel learning media to improve learning outcomes nahwu there are differences in the learning outcomes of the control group and the experimental group. Thus the spinning wheel learning